Short Communications : Pyramiding QTL for yield-related traits and grain shape in rice using single-segment substitution lines - Zhao, Fang-Ming; Zhang, Gui-Quan; Yang, Zheng-Lin; He, Guang-Hua (The Indian Journal of Genetics and Plant Breeding, 2016)
In this study, six Secondary Single-segment substitution lines (SSSLs) and five double-segment substitution lines (DSSLS) that had higher yield were produced by selective crossing of seven primary SSSLs. The DSSL-D3 had significantly higher (by 9.44%) yield than Huajingxian74, the recurrent parent. With pyramided QTL qGL3, qGWT3,qPN and the Waxy locus, the DSSL D2 showed a higher yield (by 8.70%) combined with long and high-quality grain. These results indicated that pyramiding of favourable QTL using SSSLs is feasible to improve rice yield and quality.